1989
DOI: 10.1111/j.1365-2648.1989.tb01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive behaviour: attitudes and compliance of nursing students

Abstract: As a professional, the nurse is called upon to serve as a role model for positive health behaviours. Because the practise of these behaviours may effect one's effectiveness as a role model, it is important to determine whether nurses lead a so-called preventive lifestyle and to identify what factors are predictive of compliance. Previous researchers have tended to examine individual behaviours. In this study, a prevention index was used to examine an overall preventive lifestyle. For a sample of senior year nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
2
11
0
4
Order By: Relevance
“…Despite a limited number of studies in this area, there is evidence that the task of making students adhere to healthy lifestyles is not an easy one. Soeken et al [14], for instance, found that senior-year nursing students were, in general, less compliant with preventive nutritional and lifestyle behaviour than a national sample, despite several years of education on health and health-related issues.…”
Section: The Challenge Of Adherencementioning
confidence: 96%
“…Despite a limited number of studies in this area, there is evidence that the task of making students adhere to healthy lifestyles is not an easy one. Soeken et al [14], for instance, found that senior-year nursing students were, in general, less compliant with preventive nutritional and lifestyle behaviour than a national sample, despite several years of education on health and health-related issues.…”
Section: The Challenge Of Adherencementioning
confidence: 96%
“…Soeken et al untersuchte amerikanische Pflegekräfte und stellte fest, dass 91 % massvoll beziehungsweise keinen Alkohol trinken. Untermauert wurde dies durch eine Studie von Callaghan unter chinesischen und englischen Pflegekräften, der zu einer ähnlichen Aussage kam (96 % versus 56 %) [21].…”
Section: Theoretischer Hintergrundunclassified
“…Chronische Belastungen im Arbeitsleben und im Privatleben wirkten hier möglicherweise als Verstärker von gesundheitsschädigendem Verhalten. Im Kontext dazu stand das häufige Auftreten psychovegetativer Beschwerden, wobei diese Ergebnisse denen früherer Untersuchungen an Krankenpflegepersonal entsprachen [5,19]. Daher besteht im Sinne der Qualitätssicherung Bedarf für eine arbeitnehmerfreundlichere Gestaltung der Arbeitszeiten und Arbeitsbedingungen.…”
Section: Ergebnisseunclassified
“…Hierbei kann die fachliche Kompetenz der unterschiedlichen Berufsgruppen innerhalb des Krankenhauses ausgenutzt werden, um sowohl aus medizinischer als auch aus öko-nomischer Sicht die starren Arbeitsabläufe durch Einführung und Evaluation neuer Arbeitszeitmodelle zu verbessern, von denen letztlich Personal und Patienten profitieren [10,11]. Originalarbeit Im Vergleich zu Krankenpflegepersonal aus dem Ausland [7,8,19] und der deutschen Bevölkerung [20] …”
Section: Ergebnisseunclassified